The Role of Corruption Control and Geopolitical Risks in Shaping Economic Growth of Low-Income OIC Economies - Nurul Fahana aini Harun; Nur Hayati Abd Rahman; Shafinar Ismail; Khairunnisa Abd Samad (CIVITAS (JURNAL PEMBELAJARAN DAN ILMU CIVIC), 2026)
This study investigates the relationship between control of corruption, geopolitical risks, and economic growth among low- and lower-middle-income economies within the Organisation of Islamic Cooperation (OIC). Despite the OIC’s abundance of natural and human resources, 33 out of 57 member countries remain trapped in the middle-income stage, struggling to achieve the Sustainable Development Goals (SDG 8 and SDG 16), which emphasize inclusive growth and strong institutional governance. Using annual data for 21 OIC countries from 1996 to 2023, the study employs descriptive and correlation analyses within the framework of endogenous growth theory and the political-economy growth model. The findings reveal that control of corruption, human capital, and trade openness are positively correlated with economic growth, while geopolitical risks show an insignificant relationship, suggesting that institutional and structural factors are more critical to growth than external instability. Moreover, the strong link between governance and GDP underscores the vital role of institutional quality in sustaining economic progress. Policy recommendations include strengthening anti-corruption frameworks, investing in education and human capital development, and promoting trade integration to enhance resilience against global uncertainties. Future studies should extend the analysis using dynamic panel estimation to capture the long-term effects of governance and risk on growth direction.